1996
DOI: 10.1051/jp4:1996145
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Transformation-Induced Plasticity in a Cr-Ni-Mo-Al-Ti Steel

Abstract: Abstract. This paper shows cxpcrinicn~~~l results concerning thc lnartcnsitic transcormation and the transfor1nation-in(i~1cc(I plasticity undcr multinsial loading. The matcrial investigated is a Cr-Ni-Mo-Al-Ti steel, which is suhrnitlcd to :I y--)cr.' nlartcnsitic phasc: transformation undcr an applicd strcss. The specimens are thin tubes loadcd in ~cnsion-~orsion. The ~csts wcrc specially dcsigncd to providc information on classical questions rclatcd with transforrna~ion plasricily and 111c ~ntcraction bctwc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…The term represents the orientation effect (Marketz and Fischer, 1995). Even in the case the trip strain progresses, which agrees with the experimental observation by Videau et al (1996).…”
Section: Illustrative Examplessupporting
confidence: 85%
“…The term represents the orientation effect (Marketz and Fischer, 1995). Even in the case the trip strain progresses, which agrees with the experimental observation by Videau et al (1996).…”
Section: Illustrative Examplessupporting
confidence: 85%
“…Similar to the effect of an increase in stress levels superimposed during the phase transformation, previous studies have shown that an increase in pre-strain levels prior to isothermal bainitic reactions also result in significant TP strains [1,12]. Since the occurrence of TP strains is attributed to the occurrence of external stresses superimposed during the phase transformation, transformations plasticity strains prevalent after pre-straining the specimens mostly stem from residual stress fields generated during pre-straining [32]. Since an anisotropic shape change occurs, the stress fields around the introduced dislocations seem to have a preferred alignment.…”
Section: Discussionmentioning
confidence: 85%
“…However, plastic pre-deformations with more than 10% strain tend to retard the transformation as the forming phase fronts start hindering each other [14]. In addition, TP strains were associated with the residual stresses brought about by plastic pre-deformations [32], and were different under the simultaneous application of pre-deformation and superimposed stresses below the elastic limit [19]. Thus, TP, a key parameter in the modelling of bainitic and martensitic phase transformations, deserves further investigation to uncover the roles of and the interrelationship between the governing mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…They rest on the hypothesis that only the first mechanism mentioned above operates. For martensitic transformation, more recent experimental work [40] concluded that this assumption is reasonable within a first approximation, but the model must be refined. Nevertheless, formulation of a macroscopic law for martensitic transformation plasticity in ferrous alloys is still an open question even if micromechanical models have seen outstanding developments.…”
Section: Phase Transformationsmentioning
confidence: 96%